2017
DOI: 10.1371/journal.pone.0170258
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Five Competing Strategies for the Management of Multiple Recurrent Community-Onset Clostridium difficile Infection in France

Abstract: BackgroundClostridium difficile infection (CDI) is characterized by high rates of recurrence, resulting in substantial health care costs. The aim of this study was to analyze the cost-effectiveness of treatments for the management of second recurrence of community-onset CDI in France.MethodsWe developed a decision-analytic simulation model to compare 5 treatments for the management of second recurrence of community-onset CDI: pulsed-tapered vancomycin, fidaxomicin, fecal microbiota transplantation (FMT) via co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 77 publications
3
47
0
1
Order By: Relevance
“…This has recently been shown for perceived expensive therapeutic options such as directly acting anti‐virals and with strategies for screening for hepato‐cellular cancer, among others . Other microbial strategies found to be cost‐effective are faecal microbial transplantation for C difficile . Our data are the first to determine this from a microbial diagnostic perspective in cirrhosis and could help translate this burgeoning field towards clinical practice.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This has recently been shown for perceived expensive therapeutic options such as directly acting anti‐virals and with strategies for screening for hepato‐cellular cancer, among others . Other microbial strategies found to be cost‐effective are faecal microbial transplantation for C difficile . Our data are the first to determine this from a microbial diagnostic perspective in cirrhosis and could help translate this burgeoning field towards clinical practice.…”
Section: Discussionmentioning
confidence: 77%
“…32,33 Other microbial strategies found to be cost-effective are faecal microbial transplantation for C difficile. [34][35][36] Our data are the first to determine this from a microbial diagnostic perspective in cirrhosis and could help translate this burgeoning field towards clinical practice.…”
Section: Discussionmentioning
confidence: 89%
“…In total, 9 articles were analyzed and eligible for the systematic review (Appendix B online). [44][45][46][47][48][49][50][51][52] Articles identified in literature search: 46…”
Section: Article Selectionmentioning
confidence: 99%
“…A survey showed that among patients of Crohn's disease who received FMT, 56% showed satisfactory clinical efficacy, 74% showed willingness for a second FMT, and 89% expressed willingness to recommend FMT to other patients [171]. Also, the cost efficacy of FMT has been demonstrated worldwide [172][173][174][175][176]177]. FMT is still very far from being implemented into routine therapy.…”
Section: The Importance Of Safe Fmtmentioning
confidence: 99%